An Analysis of Anti-hero Portrayed in Joker (2019) Movie by Todd Phillips - La Ode Muhamad Irwin Syawal; Ahmad Jaelani Asha; Muhammad Ikhwan Mardin; Armadani Armadani (Advances in Community Services Research, 2026)
This research aims to analyze the main character which is Arthur Fleck as anti-hero, therefore the characterization divided into 7 parts which is 1) Petty 2) Ignominious 3) Passive 4) Ineffectual 5) Dishonest, 6) Fragile and 7) Lonely. The study focuses on intrinsic parts of the movie, especially the plots in the movie that depict the character as anti-hero of the main character which is Arthur Fleck. To illustrate the characterization, the researchers apply qualitative method by using Theory of anti-hero proposed by Abrams to describe each trait from Arthur Fleck. The primary data is taken from the movie under the title “Joker (2019)” by Todd Philips. After the analysis is done, the researchers discover three characteristics of Arthur Fleck depict in the movie as anti-hero, which is lonely, fragile, and ineffectual.